Brincadeiras de crianças abrigadas : estudo etnográfico em instituição de acolhimento - Oliveira, Sonia Cristina de (2014)
The research aimed to investigate the play in the shelter of context, and knowing how the play fit or joining as an instrument of acceptance, development and learning for the social life of children. The central idea, pursued in research, focuses on research questions with the following propositions: 1) If every child plays and when he plays it brings content related to your experience? As this child "trapped" organizes and experience this playful experience? 2) If the games are determinations of social and cultural aspects, with which children references use the imagination at play as they are marked by abandonment, neglect and violence? 3) The games are activities that cater to your child's imagination as drafting losses instrument? It resulted in checking the operation of the games as they occur, how to structure, organize and experience the playful experiences and how they bring everyday elements in these activities. Anyway, what relationship does the play with your experience? It is a case study of ethnographic genre and is anchored in the soil of paradigmatic sociology of childhood and theoretical discussing the game in a sociocultural perspective. The field of research is a host institution in Cuiabá / MT, which houses and protects children up to 12 years, victims of some type of neglect or family violence. The sample involved caregivers and children 2- 5 years. The episodes were collected with observation in situations of play, notes in field diary, record video and audio. The data analysis, whose focus is on the games and the meanings on other everyday, reveals important aspects of routine, experience and history of children's lives. The research shows that the games help create emotional ties, enrich their interactions and help in the preparation of losses. The challenge to the authority and transgression are important strategies involved in the operation of games. Children fighting for autonomy in an attempt to win their space, some exercise this role through transgression, the play gives voice to children and allows actions with autonomy and authorship. The games reflect very child expressed about them, their history and about the institution, and in the process it is better to play the interaction of the goals of the institution. They simply benefit by being together, organize and experience the playful experiences around issues of the institution and your family memories. Among the many issues raised, one of them is the fact that the institutional routine and the service directly involve the organization, spontaneity and autonomy to play. The study suggests among other things, a reorganization of recreational activities, this involves logistics, more dialogue, training and planning with room for play. This may not be the most important for small, but undoubtedly occupies most of the time.